POLA KEJADIAN ISPA BALITA: KORELASI RIWAYAT IMUNISASI DAN PAPARAN ASAP ROKOK - Nainggolan, Elfrida (Ensiklopedia of Journal, 2024)
Abstract: Acute Respiratory Infections (ARI) remain one of the leading causes of morbidity and mortality from infectious diseases worldwide. Some factors that cause ARI in toddlers include immunization history and exposure to cigarette smoke. Based on data search, it is known that UPTD Puskesmas Bawomataluo is one of the health centers with the highest incidence of ARI in Nias Regency. The purpose of the study was to determine the Correlation of Immunization History and Cigarette Smoke Exposure. The study used a type of quantitative research with a cross sectional design. The research was conducted in March 2023 in Bawomataluo Village, Fanayama District, South Nias Regency. The population is mothers who have toddlers aged 1-5 years in Bawomataluo Village, Fanayama District, South Nias Regency as many as 261 people with a selected sample of 72 people. The sampling technique used Simple Random Sampling, the research instrument used a research questionnaire. Data analysis was done univariate and bivariate. The results showed there was a relationship between immunization history p value: 0.020 and exposure to cigarette smoke p value: 0.000. It is recommended to the Puskesmas to increase the achievement of complete basic immunization and parents should avoid smoking indoors and need to pay attention to household ventilation to circulate dirty air, such as cigarette smoke.Keywords: Toddlers, ARI, Cigarette Smoke Exposure, Immunization History.